Strategi Humor dalam Manzai Jepang & Double Act Indonesia: Kajian Pragmatik Lintas Budaya - Kubro, Intan Khodijatul (Japanology: The Journal of Japanese Studies, 2024)
This research examines how humor speech strategies are used in the comedy variety of Manzai Japan and Double Act Indonesia, focusing on the humor discourse that appears in the dialogue of the M-1 Grand Prix 2022 show and the Duo Komedian 2021 competition. The method used is qualitative discourse analysis, by identifying linguistic and rhetorical patterns that form humor in both shows. The data collected was then transcribed into text form, and then analyzed using the four-dimensional theory of discourse. The findings show that although both forms of comedy use similar humor strategies such as self-deprecation, humor targeted at the interlocutor, and third-party references, there are important differences in their execution and cultural nuances. Japanese Manzai often relies on quick exchanges and logical absurdity, while Indonesian double acts often use expressive gestures and socially relevant humor topics. Through Manzai plays, the Japanese tend to be more subtle and polite, whereas overly offensive humor is less likely to be accepted. While Indonesians are more expressive and open in using humor.